Diffuse Hydrothermal Venting: A Hidden Source of Iron to the Oceans - Lough, Alastair J. M.; Connelly, Douglas P.; Homoky, William B.; Hawkes, Jeffrey A.; Chavagnac, Valerie; Castillo, Alain; Kazemian, Majid; Nakamura, Ko-ichi; Araki, Tohru; Kaulich, Burkhard; Mills, Rachel A. (Frontiers in Marine Science, 2019)
Iron (Fe) limits or co-limits primary productivity and nitrogen fixation in large regions of the world’s oceans. Hydrothermal supply of Fe to the deep ocean is extensive; however most of this work has focused on examining high temperature, focused flow on ridge axes that create “black smoker” plumes. The contribution of other types of venting to the global ocean Fe cycle has received little attention. To thoroughly understand hydrothermal Fe sources to the ocean, different types of vent site must be compared. To examine the role of more diffuse, higher pH sources of venting, a hydrothermal plume above the Von Damm vent field (VDVF) was sampled for Total dissolvable Fe (unfiltered, TDFe) dissolved Fe (<0.2 µm, dFe) and soluble Fe (<0.02 µm, sFe). Plume particles sampled in-situ were characterised using scanning electron microscopy and soft x-ray spectromicroscopy. The VDVF vents emit visibly clear fluids with particulate Fe (TDFe-dFe) concentrations up to 196 nmol kg-1 comparable to concentrations measured in black smoker plumes on the Mid-Atlantic Ridge. Colloidal Fe (cFe) and sFe increased as a fraction of TDFe with decreasing TDFe concentration. This increase in the percentage of sFe and cFe within the plume cannot be explained by settling of particulates or mixing with background seawater. The creation of new cFe and sFe within the plume from the breakdown of pFe is required to close the Fe budget. We suggest that the proportional increase in cFe and sFe reflects the entrainment, breakdown and recycling of Fe bearing organic particulates near the vents. Fe plume profiles from the VDVF differ significantly from previous studies of “black smoker” vents where formation of new pFe in the plume decreases the amount of cFe. Formation and removal of Fe-rich colloids and particles will control the amount and physico-chemical composition of dFe supplied to the deep ocean from hydrothermal systems. This study highlights the differences in the stabilization of hydrothermal Fe from an off-axis diffuse source compared to black smokers. Off-axis diffuse venting represent a potentially significant and previously overlooked Fe source to the ocean due to the difficulties in detecting and locating such sites.